2017
DOI: 10.1038/ncomms15614
|View full text |Cite
|
Sign up to set email alerts
|

Human LACC1 increases innate receptor-induced responses and a LACC1 disease-risk variant modulates these outcomes

Abstract: Functional consequences for most inflammatory disease-associated loci are incompletely defined, including in the LACC1 (C13orf31) region. Here we show that human peripheral and intestinal myeloid-derived cells express laccase domain-containing 1 (LACC1); LACC1 is expressed in both the cytoplasm and mitochondria. Upon NOD2 stimulation of human macrophages, LACC1 associates with the NOD2-signalling complex, and is critical for optimal NOD2-induced signalling, mitochondrial ROS (mtROS) production, cytokine secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 55 publications
4
64
0
2
Order By: Relevance
“…Localizes to the ER While LACC1 is associated with multiple immune-mediated diseases, only a few recent studies have examined its function in mammalian cells. LACC1 has been shown to colocalize with the mitochondria, cytosol, and peroxisomes (Assadi et al, 2016;Cader et al, 2016;Lahiri et al, 2017). However, our in silico analysis by PSORTII indicated that LACC1 might also localize to the ER, and a THP-1 human macrophage cell line (unstimulated) study showed a low percentage of LACC1 localization to the ER (Assadi et al, 2016).…”
Section: Lacc1mentioning
confidence: 71%
See 4 more Smart Citations
“…Localizes to the ER While LACC1 is associated with multiple immune-mediated diseases, only a few recent studies have examined its function in mammalian cells. LACC1 has been shown to colocalize with the mitochondria, cytosol, and peroxisomes (Assadi et al, 2016;Cader et al, 2016;Lahiri et al, 2017). However, our in silico analysis by PSORTII indicated that LACC1 might also localize to the ER, and a THP-1 human macrophage cell line (unstimulated) study showed a low percentage of LACC1 localization to the ER (Assadi et al, 2016).…”
Section: Lacc1mentioning
confidence: 71%
“…Using calnexin as an ER marker, a low level of LACC1 localization to the ER was observed at baseline in MDMs through a microscopic approach (Figures 1A and 1B). As LACC1 regulates PRR-induced outcomes (Lahiri et al, 2017), we asked if PRR stimulation regulates LACC1 localization to the ER. We stimulated NOD2, a PRR associated with Crohn's disease whose ligand is the minimal component of bacterial peptidoglycan, muramyl dipeptide (MDP).…”
Section: Lacc1mentioning
confidence: 99%
See 3 more Smart Citations